2000
DOI: 10.5860/crl.61.2.127
|View full text |Cite
|
Sign up to set email alerts
|

When Questions Are Answers: Using a Survey to Achieve Faculty Awareness of the Library’s Electronic Resources

Abstract: The Utah State University (USU) Libraries spend approximately 11 percent of their materials budget on electronic resources. Because electronic resources occupy no shelf space and often are used from remote locations, it can be difficult to alert users to new resources at the library and to determine what sort of patron support is needed. This study investigated electronic database awareness and use by 856 USU administrators and teaching faculty. The responses revealed the need for greater publicity regarding n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 2 publications
1
22
1
Order By: Relevance
“…More than two-thirds of respondents were aware of some of the electronic resources. Respondents who were aware of, and made use of, each database were asked to rate the importance of that database to their own work (Weingart and Anderson, 2000). Tenner and Yang (1999) analyzed the relationship between the electronic journal use and age, and status of faculty members and found that assistant professors were most likely to have used electronic journals (44.7 per cent), followed by full professors (34.5 per cent), and associate professors (34.2 per cent).…”
Section: Evaluating Digital Libraries: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…More than two-thirds of respondents were aware of some of the electronic resources. Respondents who were aware of, and made use of, each database were asked to rate the importance of that database to their own work (Weingart and Anderson, 2000). Tenner and Yang (1999) analyzed the relationship between the electronic journal use and age, and status of faculty members and found that assistant professors were most likely to have used electronic journals (44.7 per cent), followed by full professors (34.5 per cent), and associate professors (34.2 per cent).…”
Section: Evaluating Digital Libraries: Literature Reviewmentioning
confidence: 99%
“…Weingart and Anderson (2000) have mentioned in the article they have written that only the minority of the other researches in the literature made regarding the use of the electronic resources in universities include a survey study directly related with the academicians. When we look at the studies made in the following years, on the use of the databases in the literature, we can say that this tendency remains unchanged.…”
Section: Evaluating Digital Libraries: Literature Reviewmentioning
confidence: 99%
“…Curiously, some suggested resources were already offered by the Library. This could be an indication that more effort must be made to publicize the Library's resources to the ILO community, and lends support to the view that the 'questions' posed in a user survey are an important means to achieve awareness of the Library's resources (Weingart & Anderson, 2000).…”
Section: Online Resource Usementioning
confidence: 78%
“…In assessing the relative importance researchers place on different databases, past research identified the following databases important to (or used frequently by) researchers: Current Contents, Dissertation Abstracts, EBSCOhost, ERIC, INSPEC, Medline, ScienceDirect, and Web of Science (Bar-Ilan, Peritz & Wolman, 2003;Clark & Gomez, 1990;Talja & Maula, 2003;Weingart & Anderson, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One common drawback in some of these previous studies (Bar-Ilan, Peritz, & Wolman, 2003;Weingart & Anderson, 2000) is that they did not analyze their data by discipline. For example, Weingart & Anderson (2000) found that 34.6% and 65.6% of all respondents were unaware of ERIC and Compendex Engineering Index respectively.…”
Section: Literature Reviewmentioning
confidence: 99%